CSR Website Disclosure and Company Business Performance: The Role of Corporate Reputation and Cost Leadership Strategy - Nabila Azzahra; Erna Widiastuty (Institute of Research and Community Outreach - Petra Christian University, 2025)
Research on CSR disclosure and company business performance has shown inconsistent results. Therefore, this study aims to deepen understanding by incorporating corporate reputation as a mediating variable and cost leadership strategy as a moderating variable. This study provides empirical evidence of the mediating role of corporate reputation and the moderating role of the cost leadership strategy in the influence of CSR website disclosure on company business performance. The research sample consists of non-financial companies listed on the Indonesia Stock Exchange for the 2017-2022 period. Purposive sampling techniques guided the sample selection, yielding 309 firm-year observations. We obtained the research data from Datastream Revinitiv Eikon, company websites, and company annual reports. We conducted hypothesis testing using STATA 17 software. The results of the study show that the cost leadership strategy weakens the influence of CSR website disclosure on company business performance.